Influence of Changing Rainfall Patterns on the Yield of Rambutan ( Nephelium lappaceum L.) and Selection of Genotypes in Known Drought-tolerant Fruit Species for Climate Change Adaptation - Magdalita, Pablito M.; Saludes, Ronaldo B. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 27 No 1 (2015), 2015)
In fruit crop production, rainfall, water stress, temperature, and wind are key variables for success, and the present changes in rainfall patterns could affect the flowering and yield of the rambutan (Nephelium lappaceum L). Other fruit species like macopa (Syzygium samarangense), siniguelas (Spondias purpurea), and native santol or cotton fruit (Sandoricum koetjape) remain productive despite extreme climatic changes. This study assessed the influence of rainfall on rambutan yield and evaluated and selected tree genotypes of known drought-tolerant fruit species. Rambutan yield in a selected farm in Calauan, Laguna, Philippines, dropped remarkably from 152.2 kg/tree in 2008 to 8.6 kg/tree in 2009. This reduction could be attributed to the high rainfall in April 2009 at 334.4 mm, and possibly other environmental factors like temperature, relative humidity, solar radiation, and strong wind. Furthermore, wet months in 2009 also inhibited the flowering of rambutan. However, a low yield obtained in 2010 at 45.5 kg/tree could be partly attributed to the very low rainfall in May 2010 at only 9.1 mm. On the other hand, in relation to changing climate, selection of tree genotypes for use as varieties in known drought- and flood-tolerant fruit species based on important fruit qualities like sweetness, juiciness, and high edible portion was done. Among 103 macopa genotypes, Mc-13, 43, and 91 were selected and the best (i.e. , Mc-13) had sweet (7.15 °Brix) and crispy fruits weighing 49.44 g, creamy white (RHCC 155 A), and had high edible portion (EP, 93.22%). Among 114 siniguelas genotypes, Sg-41, 42 and 105 were selected and the best selection (i.e., Sg-41), had sweet (12.50 °Brix) and juicy fruit weighing 20.42 g, ruby red (RHCC 59 A), and had high EP (83.27%). Among 101 native santol genotypes, Sn-47, 59, and 74 were selected and the best selection (i.e. , Sn-59) had relatively sweet (5.56 °Brix) and juicy fruits weighing 51.96 g, maize yellow (RHCC 21 B), and had high EP (82.20%). These selections are recommended for planting in marginal and drought-prone areas for climate change adaptation. In addition, they can fare better in flooded areas in the face of climate change since they are very hardy, and have woody and strong roots that can resist strong wind and increasing amount of rainfall brought about by climate change. Keywords: Climate change, rainfall, macopa, native santol, rambutan, siniguelas